Representation of Surrounding Communities in Iwan Simatupang's RT-Nol/RW-Nol Drama Script (Sociology of Literature Theory): Bahasa Indonesia - Haqq, Bintang Abdul; Ainaini Yusup, Khurul; Darmawan, Aditya; Taufik, Taufik; Repelita, Tridays (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2024)
This study aims to examine the influence of using the Indonesian language in academic presentations on the understanding of materials at Buana Perjuangan University. In the context of higher education, effective use of the language of instruction is crucial to ensure optimal understanding of the conveyed material. This research employs a quantitative method with a survey design. The research sample consists of 30 randomly selected students from various study programs. Data were collected through a questionnaire measuring students' level of understanding of materials presented in Indonesian compared to foreign languages such as English. According to the questionnaire results, 42% mentioned that the influence of using Indonesian in presentations enhances understanding of the materials, and 45% stated that it significantly enhances understanding when presentations are conducted in Indonesian.